Hi Brad,
I am going to factor a similar expression, 8x^{3}  27y^{3}
Much of factoring has to do with pattern recognition, looking at an expression or pattern and recognizing something. In the expression 8x^{3}  27y^{3} what I see is that everything is a cube
x^{3} and y^{3} are cubes but also 8 = 2^{3} and 27 = 3^{3}
Thus
8x^{3}  27y^{3} = (2x)^{3}  (3y)^{3}
I know how to factor a difference of cubes
a^{3}  b^{3} = (a  b)(a^{2} + ab + b^{2})
thus
(2x)^{3}  (3y)^{3} = (2x  3y)( 4x^{2} + 6xy + 9y^{2})
Now try your two problems.
Penny
